EFFECT OF PICTURE-BOOK BIBLIOTHERAPY ON ANXIETY REDUCTIONIN HOSPITALIZED CHILDREN AT ANWAR MEDIKA HOSPITAL - Tri Peni; Tri Ratnaningsih; Siti Indatul Laili (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Hospitalization is a process that requires a person to be hospitalized for treatment, until they are allowed to go home. This process often causes stress and anxiety, especially for children, because they have to adapt to a foreign environment, be separated from their families, and undergo medical treatment. The purpose of this study was to determine the effect of bibliotherapy with picture story books on reducing children's anxiety levels in the Lily Room of Anwar Medika Hospital, Sidoarjo. The research design used a Quasi-experiment with a one-group pre-test–post-test design. The population in this study were all children treated in the Lily Room of Anwar Medika Hospital. The sample was taken using an accidental sampling technique, obtaining 37 respondents. The research instrument used a questionnaire. Data were analyzed using the Wilcoxon Signed Rank Test. The results of the Wilcoxon test obtained a p-value of 0.000 <0.05, which means there is an effect of bibliotherapy with picture story books on reducing the level of hospitalization anxiety in children in the Lily Room of Anwar Medika Hospital, Sidoarjo. Bibliotherapy with picture books is highly effective in reducing anxiety in children because the text and illustrations in books are engaging and provide a distraction that can reduce anxiety.